2021
DOI: 10.37934/cfdl.13.8.4559
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Diffuser Augmented Wind Turbine

Abstract: The wind turbine power decreases at low wind speed. A flanged diffuser plays a role of a device for collecting and accelerating the approaching wind, and thus the optimization of the diffuser shape presents an important way to enhance the wind turbine power. In this work, a numerical parametric study was conducted on the diffuser to obtain the initial optimum form of flanged diffuser. Then, the Simplex algorithm is used to obtain the optimal diffuser shape starting from the obtained initial shape. Finally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The compressed fresh air is supplied from a compressor which is consist of a pressure gauge and switch control. While the fuel is equipped from the LPG gas cylinder with regulator [50][51][52].…”
Section: Experimental Setup and Procedures 21 Selection Of Burnermentioning
confidence: 99%
See 1 more Smart Citation
“…The compressed fresh air is supplied from a compressor which is consist of a pressure gauge and switch control. While the fuel is equipped from the LPG gas cylinder with regulator [50][51][52].…”
Section: Experimental Setup and Procedures 21 Selection Of Burnermentioning
confidence: 99%
“…Bending the glass progress with time and increase temperature. The cooling process [46][47][48][49] is in the same furnace and it is also gradually with the time to avoid deformation in the glass model, where the burner is extinguished and left the furnace is closed until the temperature is reduced naturally within it [50][51][52].…”
Section: Fig 2 Experimental Setupmentioning
confidence: 99%
“…Organic Rankine cycles (ORC) operate from low-temperature heat sources are commonly used for power generation. The available energy resources are solar energy, wind, biomass products, geothermal energy, surface seawater, and others, including waste heat from various thermal processes [13][14][15][16][17]. For temperature below 200 o C, Isobutene is a common working fluid, while toluene is often used at higher source temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As their oil production is far higher than that of terrestrial plants, biofuels from microalgae feedstock have been shown to be potential feedstock for future organic working fluids. Microalgae feedstock does not compete with food supplies and does not require high quality agricultural land; the supply is available continuously, it is able to grow under hasher condition, it is non-edible, and it shows highly genetically modifiable nature and fast growth rate when compared with conventional fuel [14][15][16][17][18]. In addition, the main advantages of using biofuels from microalgae as organic working fluids in an ORC system compared to a conventional fuel include the following: (i) it does not produce hazardous waste or pollution, (ii) it is carbon neutral, (iii) it produces highly biodegradable biofuels and less toxic, (iv) and it has a lower vapour pressure [19,21,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Solar reflectance greater than 95% requires a thickness of 160 m. Sweat wicking and drying are hindered. A major personal thermoregulation pathway, moisture management, in hot, humid, and sunny conditions, is essential to wick sweat away from skin and evaporate it quickly so that heat can be dissipated, and the body can cool safely [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%